ASBJOIN: uma estratégia adaptativa para consultas envolvendo operadores de junção em Linked data - Maia, Macedo Sousa (2013)
Motivated by the success of Linked Data and driven by the growing number of data sources into RDF files available on the web, new challenges for query processing are emerging, especially in distributed settings. These environments allow distributed execution of federated queries, which involve joining data provided by multiple sources, which are often unstable. In this sense, the design of new algorithms and adaptive strategies for efficiently implementing joins is a major challenge. In this paper, we present a solution to the adaptive joins execution in federated queries. The adaptative context of distributed data sources is based on statistics that are collected at runtime. For this, we use a module that updates the information in the catalog as the query is executed. The module works in parallel with the query processor.